A perfect storm: examining the synergistic effects of negative and positive emotional instability on promoting weight loss activities in anorexia nervosa - Selby, Edward A.; Cornelius, Talea; Fehling, Kara B.; Kranzler, Amy; Panza, Emily A.; Lavender, Jason M.; Wonderlich, Stephen A.; Crosby, Ross D.; Engel, Scott G.; Mitchell, James E.; Crow, Scott J.; Peterson, Carol B.; et al. (Frontiers in Psychology, 2015)
Growing evidence indicates that both positive and negative emotion potentially influence the development and maintenance of anorexia nervosa, through both positive and negative reinforcement of weight loss activities. Such reactive emotional experience may be characterized by frequent and intense fluctuations in emotion, a construct known as “emotional instability.” The purpose of this study was to investigate the association between positive emotional instability and weight loss activities in anorexia nervosa, and to investigate the synergistic effects of positive and negative emotional instability on promoting weight loss activities. Using ecological momentary assessment methods, 118 participants with anorexia nervosa reported their emotional experiences and behaviors at least six times daily over two weeks using a portable digital device. Using generalized linear modeling, results indicated that high levels of both positive and negative emotional instability, and the interaction between the two, were associated with more frequent weight-loss activities, beyond anorexia subtype and mean levels of emotional intensity. These findings indicate that when women with anorexia exhibit both high levels of both positive and negative emotional instability they are more prone to a variety of weight loss activities. The importance of addressing the role of both positive and negative emotion in anorexia treatment is discussed.